2016
DOI: 10.1007/s00268-016-3851-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Cholecystectomy: A Cost–Effectiveness Analysis at Rwanda Military Hospital

Abstract: At RMH, while laparoscopic cholecystectomy may be a more effective approach, it is also more expensive given the low caseload and high investment costs. At commonly accepted WTP thresholds, it is not cost-effective. However, as investment costs decrease and/or case volume increases, the laparoscopic approach may become favorable. Countries and hospitals should aspire to develop innovative, low-cost options in high volume to combat these barriers and provide laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
(33 reference statements)
2
24
0
3
Order By: Relevance
“…(n = 1) [62], India (n = 1) [63], Mexico (n = 1) [64],Rwanda (n = 1) [65], and South Africa (n = 1) [66]. According to the World Bank classifications, the studies were part of the following income groups: Low Income Country (n = 1) [65], Lower Middle Income (n = 2) [62,63] and Upper Middle Income (n = 12) [52-61, 64, 66]. Table 3 shows general characteristics of each study included in the review.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…(n = 1) [62], India (n = 1) [63], Mexico (n = 1) [64],Rwanda (n = 1) [65], and South Africa (n = 1) [66]. According to the World Bank classifications, the studies were part of the following income groups: Low Income Country (n = 1) [65], Lower Middle Income (n = 2) [62,63] and Upper Middle Income (n = 12) [52-61, 64, 66]. Table 3 shows general characteristics of each study included in the review.…”
Section: Plos Onementioning
confidence: 99%
“…The Center of Disease Control guidelines were used in the majority of the studies to define an SSI [52-57, 61-64, 66]. However, three studies lacked a definition of what constituted a SSI [59,60,65]. One study classified a SSI based on the wound discharge culture or other SSI suggestive signs and symptoms but these were not elaborated further [58].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Third, the cost-effectiveness of laparoscopic surgery by utilizing donated equipment could not be evaluated. As shown in a cost-effectiveness analysis of laparoscopic versus open cholecystectomy at Rwanda Military Hospital, laparoscopic surgery may not be cost-effective at commonly accepted willingness-to-pay thresholds with low case volume in LMICs, but laparoscopic surgery can be cost-effective "in settings where machinery has already been donated" [28].…”
Section: Discussionmentioning
confidence: 99%
“…Financial cost may also be an important factor in driving the selection of surgery type. 44 , 45 To examine cost-effectiveness of the RG and LG, we retrospectively reviewed the overall hospital expenditure and found that the cost of RG group was about 23,000 RMB more than that of the LG group. A recent meta-analysis reported that the RG groups cost about $ 4000 more than the LG groups.…”
Section: Discussionmentioning
confidence: 99%